The utilization of social media and the application of fiqh methods in non-Islamic countries with regard to food issues: a comprehensive review / Siti Nur Husna Abd Rahman ... [et al.] - Abd Rahman, Siti Nur Husna; Mohd Azli, Rafidah; Kamaruzaman, Mohd Asyran Safwan; Norsalim, Putera Mohd Naim (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
This article discusses the use of social media and fiqh method applications (Islamic legal Maxims) in food-related issues in non-Muslim countries. The review aims to examine how social media and fiqh method applications can assist Muslims in non-Muslim countries in selecting and identifying halal food for consumption. The article also analyses the role played by social media and fiqh method applications in helping Muslims meet their dietary needs in non-Muslim countries and maintain the sanctity of their food in situations where it may be difficult to find halal food. This study employs a qualitative approach, and data is collected specifically regarding the use of social media and fiqh method applications in selecting food in non-Muslim countries. The results show that the use of social media and fiqh method applications can help Muslims in selecting halal food and meeting their dietary needs in non-Muslim countries. However, there are still several challenges in the use of social media and fiqh method applications, such as the reliability of information and the accuracy of fiqh methods used. Therefore, this article proposes some improvements that need to be made to enhance the quality of the use of social media and fiqh method applications in food-related issues in non-Muslim countries.